Improving the Power Quality in Tehran Metro Line-Two Using the Ant Colony Algorithm - Ehteshami, H.; Javadi, S.; Shariatmadar, S. M. (Engineering, Technology & Applied Science Research, 2017)
This research aims to survey the improvement of power quality in Tehran metro line 2 using the ant colony algorithm and to investigate all the factors affecting the achievement of this goal. In order to put Tehran on the road of sustainable development, finding a solution for dealing with air pollution is essential. The use of public transportation, especially metro, is one of the ways to achieve this goal. Since the highest share of pollutants in Tehran belongs to cars and mobile sources, relative statistical indicators are estimated through assuming the effect of metro lines development and subsequently reduction of traffic on power quality index.